MCO: the national fallacy - Rusli, Mohammad Farhan (TMR Media Sdn Bhd, 2021)
"In March 2020, Malaysia introduced the first Movement Control Order (MCO) that essentially put the country to a grinding halt. It stopped everyone in their tracks and was essentially to allow the country as a whole to understand the severity of the pandemic that was descending on the world."